Modified Segmental Osteotomy for Relocation of Malpositioned Implant: Case Report - da Silva, André Luis Fernandes (J Int Oral Health, 2015)
Obtaining a good cosmetic and proper mastication in oral rehabilitation with dental implants are directly linked to the correct positioning of the implant in the alveolar bone. The malposition of the implant is a challenge in rehabilitation, which can often compromise the entire process. In cases of severely malpositioned implants, one has the option to remove it or leave it submerged under bone and gums. Another option is the modified segmental osteotomy that aims repositioning osseointegrated implant with the surrounding bone. The objective of this case report is to present a case where an implant was severely malpositioned after surgically assisted rapid maxillary expansion, requiring a modified segmental osteotomy technique to reposition it.